Redescriptions of North American Epidamaeus (Acari, Oribatida, Damaeidae) species proposed by N. Banks, H.E. Ewing, A.P. Jacot, and J.W. Wilson - Norton, Roy A.; Ermilov, Sergey G. (Zootaxa, 2021)
Early American acarologists proposed several species that have been recombined to the oribatid mite genus Epidamaeus (Damaeidae), but none has been redescribed to modern standards. These include E. puritanicus (Banks, 1906), E. michaeli (Ewing, 1909), E. globifer (Ewing, 1913), E. florida (Wilson, 1936), E. olitor (Jacot, 1937), and E. craigheadi (Jacot, 1939). We redescribe and illustrate these species, based on available type specimens and other material in various collections, and give an indication of their overall distributions. Juvenile instars are at least partly described for all except E. florida and E. olitor. Since these six collectively include the most encountered Epidamaeus species in the eastern USA, a diagnostic key is presented that also includes E. arcticola (Hammer, 1952), which is reliably recorded from eastern North America (New Hampshire) for the first time. A neotype is selected for E. michaeli, which is considered a senior subjective synonym of E. canadensis (Banks, 1909) [new syn.]. Synonymy of E. puritanicus with E. grandjeani (Bulanova-Zachvatkina, 1957) is rejected.